Towards a circular economy for PET bottle resin using a system dynamics inspired material flow model. (10th January 2023) - Ghosh, Tapajyoti; Avery, Greg; Bhatt, Arpit; Uekert, Taylor; Walzberg, Julien; Carpenter, Alberta
Abstract: A massive rise in single-use plastic consumption has resulted in uncontrollable terrestrial and marine plastic pollution. Waste management systems currently do not have sufficient capacity to safely dispose of waste plastic. Apart from the plethora of negative environmental impacts due to mismanaged plastic waste both inland and in the oceans, landfilled plastics represents a significant recoverable energy footprint disposed of after a single use or a very short lifetime. Recovering these materials could reduce their carbon footprint by displacing the production of virgin plastic. The goal of this research is to develop a plastics circular economy framework that includes critical technological, economic, and policy constraints to help decision makers compare end of life options and inform investment decisions. In addition to implementing metrics for measuring circularity, the framework employs life cycle assessment to compare the environmental impact of pathways for improving circularity in the plastics economy. A case study exploring the recycling of polyethylene terephthalate (PET) bottles from 2020 to 2049 reveals that chemical recycling using glycolysis along with improved collection systems through drop-off recycling centers will significantly improve the circularity of PET bottles as well as reduce carbon footprints by displacing virgin PET manufacture. While waste incineration rather than recycling shows improved landfill-diversion-based circularity potential, it results in a significant increase of greenhouse gas emissions due to the combustion process. Graphical abstract: Image 1